2018
DOI: 10.1007/s11069-018-3431-8
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid clustering-fusion methodology for land subsidence estimation

Abstract: This is an author-produced, peer-reviewed version of this article. The final, definitive version of this document can be found online at Natural Hazards, published by Springer. Copyright restrictions may apply. AcknowledgmentsThe authors would like to thank Dr. Maryam Dehghani for providing the dataset used in this study. AbstractA hybrid clustering-fusion methodology is developed in this study that employs Genetic Algorithm (GA) optimization method, k-means method, and several soft computing (SC) models to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The accuracy of the prediction model is affected by the spatial heterogeneity of the factors. The K-means clustering algorithm can reduce the influence of spatial heterogeneity when the ground deformation is predicted in a large area, which is a practical method to deal with the heterogeneity problem [31].…”
Section: K-means Clusteringmentioning
confidence: 99%
“…The accuracy of the prediction model is affected by the spatial heterogeneity of the factors. The K-means clustering algorithm can reduce the influence of spatial heterogeneity when the ground deformation is predicted in a large area, which is a practical method to deal with the heterogeneity problem [31].…”
Section: K-means Clusteringmentioning
confidence: 99%
“…Algorithm refinement has been proposed to minimize the effects of residual topography (Gaber et al, 2017), large perpendicular baselines and strong temporal decorrelation (Foroughnia et al, 2019) and to assess the interferometric coherence to baselines, doppler difference, land surface evolution and polarization (Engelbrecht et al, 2014). Hybrid methods, fusing different methodological approaches have been proposed to better estimate land subsidence over noisy pixels (Chi et al, 2021;Neely et al, 2020;Taravatrooy et al, 2018) and for rural areas (Sadeghi et al, 2012). Gheorghe and Armas (2015) presented a comparison between the most popular MT-InSAR methods that are used for subsidence analysis, i.e., the PS and SBAS techniques, the first one more suitable for studying infrastructure behaviour, the latter for long-term geological patterns.…”
Section: Technical Papermentioning
confidence: 99%
“…Therefore, the use of machine learning to simulate land subsidence has become a frontier research direction in recent years. Taravatrooy et al [32] fused the k-means method, soft computing models and other approaches. The research further demonstrated that a fusion method was more accurate than the traditional methods.…”
Section: Introductionmentioning
confidence: 99%